5D Hyperchaotic Image Encryption Scheme Based on Fibonacci Q-Matrix - Geeta Biban; Renu Chugh; Anju Panwar; Mohammad Sajid (Complexity)
This article proposed an image encryption scheme along a novel five-dimensional hyperchaotic system and a Fibonacci Q-matrix (FQ-matrix) for gray images. This designed algorithm follows two key stages: the confusion stage and the diffusion stage. In the confusion step and diffusion step, the placement of the plain image pixels is replaced by a 5D hyperchaotic map and pixel values are changed using the FQ-matrix, respectively. The fortitude of the designed encryption scheme is concluded by countering the algorithm on statistical analysis like histogram analysis, chi-square test, correlation coefficient analysis, information entropy analysis, differential attacks (NPCR, UACI), and NIST suite test. The produced algorithm’s experimental evaluation indicates that the entropy, NPCR, and UACI values tend to be ideal values. The numerous analyses indicate that the proposed algorithm has a lot of characteristics like the low correlation of adjacent cipher pixels, strong security, and large key space, which can give high confidentiality in image data.